"Vulnerable, " "At-risk, " "Disadvantaged": How A Frameworkfor Recreation in Canada 2015: Pathways to Wellbeing Reinscribes Exclusion. Issue 2 (2nd April 2020) - Tink, Lisa N.; Peers, Danielle; Nykiforuk, Candace I. J.; Kingsley, Bethan C.
ABSTRACT: The purpose of this paper is to analyze how the problem of exclusion and the solution of inclusion have been discursively produced within A Framework for Recreation in Canada 2015: Pathways to Wellbeing. Centred around three main arguments, our analysis demonstrates the ways in which the Framework strategically combines notions of Otherness with discourses of risk and inclusion in order to target social groups that are perceived to be lacking the personal, cultural, or material resources to participate in the specified amount of physical activity required for health (and thus national economic) benefits. By interrogating the ways the Framework has enacted a particular Canadian 'brand(ing)' of inclusion, our analysis challenges recreation professionals (including academics) to think outside the inclusion/exclusion binary and consider their complicity in the creation, and maintenance, of exclusionary practices.